2016
DOI: 10.1080/14740338.2016.1238071
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors and risk ofClostridium difficileinfection: a multi-country study using sequence symmetry analysis

Abstract: Our study confirms the association between PPI initiation and C. difficile infections across countries in the Asia-Pacific region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Also, control group n = 17,217 in the test group; n = 286,018 in the control group Recurrent CDI occurred in n = 1279; n = 5459 in the control group Laboratory confirmation of C. diff or clinical definition. No further detail provided PPI use increased risk for initial CDI episode (random effects model, overall OR 2.34, 95% CI 1.94–2.82; p < 0.00001) Age-stratified subgroup analyses: significant associations between PPI use and initial CDI episode in adults (OR 2.30, 95% CI 1.89–2.80; p < 0.00001) and pediatrics (OR 3.00, 95% CI 1.44–6.23; p < 0.00001) Roughead et al [ 36 ] 2008–2013 (insurance database) 1996–2014 (hospital dataset) Retrospective data from worker insurance database and a hospital in-/outpatient dataset from a single center 1.2 million patient records examined and sequence symmetry analysis used to assess PPI use as risk factor for CDI n = 310 patients received PPIs and oral vancomycin (proxy indicator for CDI) Positive association between PPI use and CDI (adjusted sequence ratio for insurance dataset 5.40; 95% CI 2.73–8.75 and for hospital dataset 3.21; 95% CI 2.12–4.55) Sadahiro et al [ 63 ] May 2008–October 2011 Prospective, single-center RCT comparing oral antibiotics and probiotics pre surgery to prevent infection n = 310 Colon cancer No change in detection of C. diff toxin across three treatment groups (probiotics; antibiotics; control (no probiotics or antibiotics)) Assessment of C. diff toxin (A and B) in stool samples by RIDASCREEN Rates of CDI increased post-operatively in all groups (probiotic group, from 2.0% to 7.0%; antibiotic group, 5.1% to 9.1%; control group, 2.1% to 10.5%) Sasabuchi et al [ 28 ] July 2010–March 2013 Retrospective cohort study using the Japanese Diagnosis Procedure Combination database (multicenter) n = 15,651 receiving prophylaxis n = 15,651 controls Severe sepsis and receiving stress ulcer prophylaxis within 2 days of hospital admission; propensity-matched controls did not receive prophylax...…”
Section: Resultsmentioning
confidence: 99%
“…Also, control group n = 17,217 in the test group; n = 286,018 in the control group Recurrent CDI occurred in n = 1279; n = 5459 in the control group Laboratory confirmation of C. diff or clinical definition. No further detail provided PPI use increased risk for initial CDI episode (random effects model, overall OR 2.34, 95% CI 1.94–2.82; p < 0.00001) Age-stratified subgroup analyses: significant associations between PPI use and initial CDI episode in adults (OR 2.30, 95% CI 1.89–2.80; p < 0.00001) and pediatrics (OR 3.00, 95% CI 1.44–6.23; p < 0.00001) Roughead et al [ 36 ] 2008–2013 (insurance database) 1996–2014 (hospital dataset) Retrospective data from worker insurance database and a hospital in-/outpatient dataset from a single center 1.2 million patient records examined and sequence symmetry analysis used to assess PPI use as risk factor for CDI n = 310 patients received PPIs and oral vancomycin (proxy indicator for CDI) Positive association between PPI use and CDI (adjusted sequence ratio for insurance dataset 5.40; 95% CI 2.73–8.75 and for hospital dataset 3.21; 95% CI 2.12–4.55) Sadahiro et al [ 63 ] May 2008–October 2011 Prospective, single-center RCT comparing oral antibiotics and probiotics pre surgery to prevent infection n = 310 Colon cancer No change in detection of C. diff toxin across three treatment groups (probiotics; antibiotics; control (no probiotics or antibiotics)) Assessment of C. diff toxin (A and B) in stool samples by RIDASCREEN Rates of CDI increased post-operatively in all groups (probiotic group, from 2.0% to 7.0%; antibiotic group, 5.1% to 9.1%; control group, 2.1% to 10.5%) Sasabuchi et al [ 28 ] July 2010–March 2013 Retrospective cohort study using the Japanese Diagnosis Procedure Combination database (multicenter) n = 15,651 receiving prophylaxis n = 15,651 controls Severe sepsis and receiving stress ulcer prophylaxis within 2 days of hospital admission; propensity-matched controls did not receive prophylax...…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an increased risk of clostridium difficile infection in nonhospitalized patients on PPIs therapy occurs. Recently, a multi-country study, confirmed the association between PPI exposure and clostridium difficile infections across Australia, Korea, Taiwan, Japan and Canada (20). Overall, PPI therapy within a short course may be useful in selected patients.…”
Section: Potential Risk Of Infectionsmentioning
confidence: 89%
“…There are several reports concerning the potential risk of critical infections among individuals treated with PPI agents. In PPI users, enteric infections such as clostridium difficile colitis (7,20) and pulmonary infection (8) could be particularly frequent. The mechanisms underlying predisposition of infections associated to PPI exposure are not exactly clear (1).…”
Section: Potential Risk Of Infectionsmentioning
confidence: 99%
“…While PPIs are generally well tolerated, their use has been linked to an increased risk of several adverse outcomes [10][11][12][13][14][15]. Clinical guidelines recommend that patients receive treatment for 4 to 8 weeks on standard strength PPIs and step down to a lower strength or discontinue treatment thereafter.…”
Section: Introductionmentioning
confidence: 99%